CLINICAL FEATURES OF COMMON INFECTIONS IN CHILDREN UNDER 14 YEARS OF AGE WITH HIV (Multidisciplinary Journal of Science and Technology, 2026)
Studying the clinical course of co-infections (opportunistic infections) in children infected with the human immunodeficiency virus is one of the most pressing issues in pediatric and infectious disease practice. This study evaluates the frequency and clinical manifestations of respiratory, gastrointestinal, and systemic co-infections in HIV-infected children under 14 years of age. Retrospective and prospective analyses revealed that against the background of immunodeficiency, concurrent pathologies exhibit atypical, chronic, and recurrent patterns, often showing resistance to conventional therapy. The conceptual findings serve to optimize local pediatric management protocols and reduce morbidity rates in the region.